Evaluation of the Asymmetry of Leg Muscles Forces in the Subjects with Anterior Cruciate Ligament Reconstruction - Sharifmoradi, Keyvan; Karimi, Mohammad Taghi; Hoseini, Yasin (The Journal of Knee Surgery, 2019)
Running asymmetry has not been assessed among patients with anterior cruciate ligament (ACL) deficiency. The aim of this study was to evaluate the spatiotemporal and muscle force asymmetry indexes in the subjects with ACL reconstruction (ACLR) compared with normal subjects. Eight individuals with a reconstructed ACL and eight individuals with intact ACLs were participated in this study. A Vicon motion analysis system and two Kistler force plates were used to record data. Muscle forces analysis was done by the use of OpenSim software. The results of this study showed that ACLR group had a significant weakness in hip abductor, extensor, and adductor muscles of the affected limb compared with healthy subjects (p < 0.05). In ACLR group, asymmetry of gluteus minimus muscle force was significantly greater than that of healthy group (p = 0.04). After the reconstruction of the ACL, there is still a significant asymmetry in muscle force as well as a reduction in force production of ACLR group especially in reconstructed side which put a person at high risk of reinjuries. Thus, strengthening of these muscles on the affected side to increase running performance of ACLR group is recommended.
Keywords: muscle force; ACL; asymmetry; running